Formula supplementation with human and bovine milk oligosaccharides modulates blood IgG and T-helper cell populations, and ex vivo LPS-stimulated cytokine production in a neonatal preclinical model - Monaco, Marcia H.; Wang, Mei; Hauser, Jonas; Yan, Jian; Dilger, Ryan N.; Donovan, Sharon M. (Frontiers in Immunology, 2023)
Introduction Human milk contains structurally diverse oligosaccharides (HMO), which are multifunctional modulators of neonatal immune development. Our objective was to investigate formula supplemented with fucosylated (2’FL) + neutral (lacto-N-neotetraose, LNnt) oligosaccharides and/or sialylated bovine milk oligosaccharides (BMOS) on immunological outcomes. Methods Pigs (n=46) were randomized at 48h of age to four diets: sow milk replacer formula (CON), BMOS (CON + 6.5 g/L BMOS), HMO (CON + 1.0 g/L 2’FL + 0.5 g/L LNnT), or BMOS+HMO (CON + 6.5 g/L BMOS + 1.0 g/L 2’FL + 0.5 g/L LNnT). Blood and tissues were collected on postnatal day 33 for measurement of cytokines and IgG, phenotypic identification of immune cells, and ex vivo lipopolysaccharide (LPS)-stimulation of immune cells. Results Serum IgG was significantly lower in the HMO group than BMOS+HMO but did not differ from CON or BMOS. The percentage of PBMC T-helper cells was lower in BMOS+HMO than the other groups. Splenocytes from the BMOS group secreted more IL-1β when stimulated ex vivo with LPS compared to CON or HMO groups. For PBMCs, a statistical interaction of BMOS*HMO was observed for IL-10 secretion (p=0.037), with BMOS+HMO and HMO groups differing at p=0.1. Discussion The addition of a mix of fucosylated and sialylated oligosaccharides to infant formula provides specific activities in the immune system that differ from formulations supplemented with one oligosaccharide structure.